The Role of Regional Government in Maintaining the Agricultural Sector Amidst the Development of the Brebes Regency Industrial Area - Syahwa Happy Kartika Putri; Nunik Nurhayati (Proceeding International Conference Restructuring and Transforming Law, 2023)
The purpose of this study is to obtain answers to research problems based on the formulation of the problems that have been proposed. So the purpose of this study is to determine the authority of the local government in achieving the goals of regional industrial development and to find out the government's efforts in maintaining the agricultural sector in the midst of the development of the Brebes Regency industrial area. The approach taken in this research is an empirical juridical approach or can also be called sociological legal research or field research. Empirical legal research is legal research intended to examine and analyze the work of law in society. Industrial estates in fact should not be built on productive land so as not to affect the agricultural output of the surrounding community which can have a negative impact on the income of local people who will be used as industrial estate areas. With the establishment of Brebes Regency as an industrial area, there are factors that need to be considered, because Brebes Regency has a very qualified agricultural sector and is one of the largest livelihoods of its people.